Herbal Drinks to Increase Immunity in the Covid-19 Pandemic - Lubis, Rahayu; Jemadi, Jemadi; Rasmaliah, Rasmaliah (Talenta Publisher, 2022)
The Corona virus disease (Covid-19) pandemic has infected more than 252 million people in the world by the end of 2021. The first case of Covid-19 occurred in Indonesia in early March 2020, and continues to grow to reach 4.2 million cases in November 2021 with the number of deaths was 143 people (3.4%). There were 8973 cases of Covid-19 in North Sumatra Province with 294 deaths. Data from Deli Serdang Regency shows that there is an increase in Covid-19 cases being treated at hospitals. Hamparan Perak District, especially Klumpang Village, is a green zone. Therefore, it is necessary to take preventive measures against corona virus infection in the community. The strategy that can be done to increase body immunity is to train the PKK group to make drinks with herbs that are commonly found in the kitchen such as ginger, cinnamon, cardamom, black cumin, star anise, pandanus, lemongrass and so on so that it can be practiced in the family and the wider community. . The purpose of this service is to train a group of PKK mothers in Klumpang Village, Hamparan Perak District, Deli Serdang Regency to make herbal drinks to increase body immunity as an effort to prevent Covid-19. The reason for choosing this service location is because of active community participation. The participants of this service were attended by 20 people from PKK. The service activity was preceded by filling out a questionnaire before the training. This type of training has two stages, namely the first is lectures and questions and answers about the benefits of health drinks to increase body immunity, then direct practice is carried out on how to make these herbal drinks. After that, the same questionnaire was given back to be filled out by the PKK group of women. There was an increase in the knowledge of community service participants in Klumpang Village, Hamparan Perak District, Deli Serdang Regency before and after the training by 15.8%. The next hope is that this herbal drink product can be a business opportunity to help the family's economy